Penerapan Pendekatan Culturally Responsive Teaching Terintegrasi Etnokimia dalam Mengembangkan Keterampilan Siswa Abad 21 pada Materi Hidrolisis di MAN 1 TIKEP - Irfan H. Arif; Asmin Lukman; Zulkifli I. Tuara (Jurnal Ilmiah Wahana Pendidikan, 2021)
Education is a conscious and planned effort to create an atmosphere of learning and the process so that students actively develop their potential to have spiritual, religious, self-control, personality, intelligence, noble character, and skills needed by themselves, in society, nation, and state. Observations show that in MAN 1 Tikep, the chemistry learning process in schools is still value-oriented without paying attention to other skills, including 21st-century skills. The purpose of this study is to integrate ethnochemistry through the Culturally Responsive Teaching approach and develop 21st-century students' skills through a Culturally Responsive approach. TeachingIntegrated Ethnochemistry on Hydrolysis material. The Culturally Responsive Teaching approach is a multicultural branch of science, it can be interpreted that the Culturally Responsive Teaching approach is the right way to implement multicultural education in the classroom (learning process). The goal of the Culturally Responsive Teaching approaches that all students can involve themselves to participate actively in the learning process. The method used in qualitative descriptive approach research can produce descriptive data in the form of written or spoken words from people on observed behavior, this approach is directed at the background and the individual holistically with this qualitative approach the researcher will find it easier to apply, analyze 21st -century skills with an integrated ethnochemical culturally responsive teaching approach on hydrolysis material in MAN 1 Tikep, sampling in this study using purposive sampling data collection techniques using interviews, classroom observation, reflective journals, and documentation. Data analysis is qualitative data analysis, which is presenting data starting from examining all collected data, compiling it, then proceeding to the next stage, checking its validity and interpreting it by analyzing the ability of reason to make decisions. The results showed that with the ethnochemical integrated culturally responsive teaching approach on hydrolysis material in developing 21st-century skills, students indicated that students 'learning development was increasing in understanding the concept of hydrolysis material because learning that took place besides conveying theory, there was also practicum without experiment that directly involved students' culture. The culturally responsive ethnochemical integrated teaching approach in learning is an approach that is integrated with student culture and linked to chemistry so that students understand what the teacher says and learning looks more meaningful.